APLIKASI KASCING DAN PUPUK KANDANG AYAM DALAM MEMPERBAIKI BAHAN ORGANIK TANAH SERTA PERTUMBUHAN KEDELAI - Putro Hairutomo Setiko; Joko Santoso; Yudi Yusdian; Endang Kantikowati (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2021)
The productivity of soybean nowadays is inversely related to the harvest area. The increasing area of ??soybean crops is not matched by production. Based on this, research was needed to increase soybean production, especially for soil types with low C/N ratio. The choice of this soil type is because soybeans are generally cultivated intensively. The current productivity of soybeans was low is one of which is thought to be due to a lack of organic matter and too fast nitrogen losses. The research was conducted in a demonstration plot (in a polybag in a plastic house) using a randomized complete block design, consisting of 7 treatments (A = control; B = 30 g vermicompost/polybag; C=60g vermicompost/polybag; D = 90 g vermicompost/polybag; E = 30 g poultry manure/polybag; F = 60 g poultry manure/polybag; G = 90 g poultry manure/polybag), with 4 repetitions. The results showed that the treatment of vermicompost and poultry manure significantly increased the growth and yield of soybean when compared to the control. A dose of 90 g poultry manure is recommended for applicated in farm because it can significantly increase soil C/N ratio, growth and yield of soybean.